A non-radioactive electrophoretic mobility shift assay for the detection of heat shock element (HSE)-binding activity in Neurospora crassa - U Meyer; L RENSING (Fungal Genetics Reports, 1998)
A non-radioactive electrophoretic mobility shift assay based on the digoxigenin detection system had been developed and applied to the analysis of the interaction between the heat shock transcription factor and the heat shock element of N. crassa.